Unilateral twin tubal pregnancy: a case report and review of the literature - Betti, Marta; Vergani, Patrizia; Damiani, Gianluca Raffaello; Pellegrino, Antonio; Di Naro, Edoardo; Trojano, Giuseppe; Pirovano, Cecilia; Stomati, Massimo; Loverro, Matteo (Acta Biomedica Atenei Parmensis, 2018)
Background: Unilateral twin tubal pregnancy is an extremely rare condition, occurring in 1/20.000-250.000 pregnancies and represents a major health risk for reproductive-aged women, leading to even life-threatening complications. Aim: We present a case of a 31-year-old woman with unilateral twin tubal pregnancy, treated with methotrexate and then surgically because of failure, followed by review of the literature. Methods: Researches for relevant data were conducted utilizing multiple databases, including PubMed and Ovid. Results: The most common type of twin ectopic pregnancy is the heterotopic (1/7000 pregnancies) in which in which both ectopic and intrauterine pregnancy occur simultaneously. Expectant, medical and surgical therapy have similar success rates in correctly selected patients. Two prospective randomized trials did not identify any statistically significant differences between groups receiving MTX as a single dose or in multiple doses. Among the 106 cases reported in literature, methotrexate was tried just in 4 patients (3 unilateral and 1 bilateral) before ours. Details are reported in the table 1. Conclusion: The recent shift in the treatment of singleton ectopic pregnancies to the less invasive medical therapy might apply even in the case of twin implants.